PENGARUH CITRA PERUSAHAAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA PT WAHANA PRESTASI LOGISTIK CABANGSUMUR BATU JAKARTA PUSAT - Imelda Imelda; Syahrul Reza (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study is to see how corporate image and service quality affect customer loyalty in pt Wahana logistics. The method the writer USES for research is a quantitative method intended to collect data. The data- collection technique used is primary data which USES a technical questionnaire through Google form. The distribution of the questionnaires as many as 99 samples, the results of this study show that a company's image and service quality are affected by customer loyalty. This research shows that the respondent response index 1. The company brand of PT Wahana Cabang Sumur Batu has predicted value or interpretation score of 4.01 with "good" characteristics 2. The quality of the service to the PT Wahana has a 4.05 value value with a "good" interpretation. 3. Customer loyalty in PT Wahana has a 3.88 score score score score on a "good" category. Beyond the assessments of the respondents' predictions, the results of the validity of the company's image variables, the quality of service and loyalty of customers are greater than the rtables which state that the respondents agree with the statement on the questionnaire.